Neurofibromatosis 1/Idiopathic eruptive macular pigmentation. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
In the first years peripheral neurofibromatosis can occur only with café-au-lait spots. Some diagnostic problems can then arise with idiopathic eruptive macular pigmentation: hence the need for a differentiation between the two conditions.